2003
DOI: 10.4049/jimmunol.170.10.5281
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Peptide-Induced Cytokine and Chemokine Expression in THP-1 Monocytes Is Blocked by Small Inhibitory RNA Duplexes for Early Growth Response-1 Messenger RNA

Abstract: In Alzheimer’s disease (AD) one finds increased deposition of Aβ and also an increased presence of monocytes/macrophages in the vessel wall and activated microglial cells in the brain. AD patients show increased levels of proinflammatory cytokines by activated microglia. Here we used a human monocytic THP-1 cell line as a model for microglia to delineate the cellular signaling mechanism involved in amyloid peptides (Aβ1–40 and Aβ1–42)-induced expression of inflammatory cytokines and chemokines. We observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 62 publications
8
138
0
1
Order By: Relevance
“…In contrast, the constitutive promoter activity seems to rely on other transcription factors. Among the potential regulators of the NLRP2 gene, we showed that Stat3 and Gfi1 did not modify the promoter activity, but other factors including Egr-1, which promotes the expression of inflammatory cytokines (29), or Sp1, a proinflammatory protein involved in the expression of mediators of inflammation (30), should be considered in future studies. Because NLRP2 inhibits NF-B, upregulation of NLRP2 may be part of a negative regulatory loop induced via inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, the constitutive promoter activity seems to rely on other transcription factors. Among the potential regulators of the NLRP2 gene, we showed that Stat3 and Gfi1 did not modify the promoter activity, but other factors including Egr-1, which promotes the expression of inflammatory cytokines (29), or Sp1, a proinflammatory protein involved in the expression of mediators of inflammation (30), should be considered in future studies. Because NLRP2 inhibits NF-B, upregulation of NLRP2 may be part of a negative regulatory loop induced via inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…A small interfering RNA (siRNA) oligonucleotide that successfully targeted Egr-1 mRNA for degradation was published for human microglial cells (Giri et al, 2003). Using software provided by Ambion (Austin, TX), oligonucleotides for the homologous mouse sequence were designed.…”
Section: Plasmid Cloning and Mutagenesismentioning
confidence: 99%
“…Small interfering RNA specific to the human Egr-1 gene has been used by others to effectively knockdown Egr-1 mRNA levels (Giri et al, 2003). As shown Figure 4A, insulin treatment results in a 2.6 fold increase in Egr-1 protein that is not affected by the presence of sequence absent in the mouse genome (scrambled siRNA; 3.0 fold induction).…”
Section: Egr-1 Is Necessary For the Insulin-induced Increase In Gnrh mentioning
confidence: 99%
“…In particular, MCP-5 was increased ϳ40-fold (range, 10 to 150) ( Figure 8). Because MCP-1 30 and FIII [31][32][33] genes have been described as targets of the transcription factor Egr-1, expression of the latter was measured and found to be increased ϳ4-fold in Tg macrophages relative to non-Tg ones (Figure 8). Together, these results indicate that N1 EC -expressing macrophages produce enhanced levels of pro-angiogenic molecules.…”
Section: Molecular Alterations In Macrophages Of Cd4c/ N1 Ec Tg Micementioning
confidence: 99%
“…This activation is also supported by the increased expression of the Egr-1 transcription factor in Tg macrophages. Egr-1 seems to be a stress-responsive gene, 55 and its activation regulates the expression of several proangiogenic genes, 56 -58 including MCP-1 30 and FIII [31][32][33]59 (see below). The reprogramming of macrophages by N1 EC must be unique, because no other signaling molecule has yet been described, to our knowledge, as being able to confer to macrophages the angiogenic properties observed in these Tg mice.…”
Section: The Pathogenesis Of the Liver Vascular Disease Of Cd4c/n1 Ecmentioning
confidence: 99%